The effectiveness and effects of alcohol regulation: Evidence from India - Dara Lee Luca; Emily Owens; Gunjan Sharma (IZA Journal of Development and Migration, 2019)
We provide quasi-experimental evidence on the effects of alcohol regulation on alcohol consumption and associated public health outcomes using detailed individual level and aggregate data from India, where state-level laws regulating the minimum legal drinking age generate substantial variation in the availability of commercially produced alcohol across people of different ages. We find that despite significant law evasion, men who are legally allowed to drink are substantially more likely to consume alcohol. Further, men who are legally allowed to drink are significantly more likely to commit violence against their partners, suggesting a causal channel between alcohol consumption and domestic violence. These results are robust to the exclusion of states with prohibition, implying that they are driven by differences in MLDA. We also examine the effects of alcohol regulation on other public health outcomes. Consistent with the existing literature, we find evidence that smoking and drinking are complements. Finally, we provide suggestive evidence that stricter alcohol control is associated with lower rates of motor vehicle accidents and crimes against women, but not other forms of crime.
Keywords: I18; K42; J12; 330; Alcohol consumption; Domestic violence; Violence against women; Prohibition; Minimum legal drinking age; Smoking; Motor vehicle accidents